Spanish Pediatric Inflammatory Bowel Disease Diagnostic Delay Registry: SPIDER Study From Sociedad Española de Gastroenterología, Hepatología y Nutrición Pediátrica - Jiménez Treviño, Santiago; Pujol Muncunill, Gemma; Martín-Masot, Rafael; Rodríguez Martínez, Alejandro; Segarra Cantón, Oscar; Peña Quintana, Luis; Armas Ramos, Honorio; Eizaguirre Arocena, Francisco Javier; Barrio Torres, Josefa; García Burriel, José Ignacio; Ortigosa Castillo, Luis; Donat Aliaga, Ester; et al. (Frontiers in Pediatrics, 2020)
Background and Aims: Diagnostic delay is especially relevant in children with Inflammatory Bowel Disease, leading to potential complications. We examined the intervals and factors for Diagnostic Delay (DD) in the Pediatric Population of Spain. Methods: We conducted a multicentric prospective study including 149 Pediatric Inflammatory Bowel Disease (PIBD) patients, obtaining clinical, anthropometric, and biochemical data. Time to diagnosis (TD) was divided into several intervals to identify those where the DD was longer and find the variables that prolonged those intervals. Missed opportunities for diagnosis (MOD) were also identified. Results: Overall TD was 4.4 months (IQR 2.6-10.4), being significantly higher in Crohn's Disease (CD) than in Ulcerative Colitis (UC) [6.3 (IQR 3.3-12.3) vs 3 (IQR 1.6 -5.6) months, p=0.0001). Time from the visit to the first physician until referral to a Pediatric Gastroenterologist (PG) was the main contributor to TD [2.4 months (IQR 1.03-7.17) in CD vs 0.83 months (IQR 0.30-2.50) in UC, p=0.0001]. One hundred and ten patients (78.3%) visited more than one physician (29.9% to 4 or more) and 16.3% visited the same physician more than 6 times before being assessed by the PG. The number of MOD was significantly higher in CD than in UC patients: 4 MOD (IQR 2-7) vs 2 MOD (IQR (1-5), p = 0.003. Referral by pediatricians from hospital care allowed earlier IBD diagnosis [OR 3.2 (CI 95% 1.1-8.9), p = 0.025]. Conclusions: TD and DD were significantly higher in CD than in UC. IBD patients (especially those with CD) undergo to a large number of medical visits until the final diagnosis.